2020
DOI: 10.1016/j.bpsc.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Hippocampal Recruitment Supports Preserved Episodic Memory in Autism Spectrum Disorder

Abstract: Background.-The degree to which individuals with autism spectrum disorder (ASD) evidence impairments in episodic memory relative to their typically developing (TD) counterparts remains unclear. According to a prominent view, ASD is associated with deficits in encoding associations between items and recollecting precise context details. Here, we evaluated behavioral and neural evidence for this impaired relational binding hypothesis using a task involving relational encoding and recollection during fMRI.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 66 publications
4
25
1
2
Order By: Relevance
“…Analysis of the LPC old/new effect showed similar latency and duration in both groups, with a spatial extension to Midline Parietal ROI in the ASD compared to TD group. First, this additional parietal recruitment may suggest a compensatory process, that is, effortful retrieval of associative information, in some similarly with Hogeveen et al [2019] study showing a hippocampal hyperrecruitment due to lower memory strength for individual items—indexed by the reduced FN400 familiarity signal. Second, the pattern of electrophysiological processes—that is, reduced amplitude of the FN400 familiarity potential, while similar amplitude but parietal extension of the LPC recollective potential—may reflect an immature development of memory processes in ASD.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Analysis of the LPC old/new effect showed similar latency and duration in both groups, with a spatial extension to Midline Parietal ROI in the ASD compared to TD group. First, this additional parietal recruitment may suggest a compensatory process, that is, effortful retrieval of associative information, in some similarly with Hogeveen et al [2019] study showing a hippocampal hyperrecruitment due to lower memory strength for individual items—indexed by the reduced FN400 familiarity signal. Second, the pattern of electrophysiological processes—that is, reduced amplitude of the FN400 familiarity potential, while similar amplitude but parietal extension of the LPC recollective potential—may reflect an immature development of memory processes in ASD.…”
Section: Discussionmentioning
confidence: 75%
“…Second, the item recognition phase in the Hogeveen et al's [2019] study may have reinforced item memory during the subsequent associative recognition phase, as previously demonstrated in elderly TD participants who show binding difficulties [Fine, Shing, & Naveh‐Benjamin, 2018]. Third, only participants who did not show fatigue were tested on the associative recognition phase of Hogeveen et al's [2019] study, which may limit their conclusion that all participants showed preserved relational memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explain these findings, Bowler et al [2011] suggested that ASD is characterized by difficulties in relational binding , which gives rise not only to the patterning of memory difficulties described above, but also to other difficulties experienced by autistic people, such as difficulty in mentalizing and problems in utilizing meaning in support of recall [Bowler, Matthews, & Gardiner, 1997; Cooper & Simons, 2019]. Bowler et al [2011] also drew on current neural models of relational binding in episodic memory [Davachi, 2006; Opitz, 2010] to suggest a possible fronto‐hippocampal basis for these difficulties [see Hogeveen, Krug, Geddert, Ragland, & Solomon, 2020; Cooper et al, 2017; Gaigg, Bowler, Ecker, Calvo‐Merino, & Murphy, 2015 for supporting evidence].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence is not consistently in favor of specific difficulties in relational memory since some studies have revealed general difficulties in memory for both features in combination and isolation [Cooper et al, 2015; Ring, Gaigg, & Bowler, 2016; Solomon, McCauley, Iosif, Carter, & Ragland, 2016]. In addition, the results of a recent study of young adults with ASD indicate preserved relational memory and memory for single features in ASD resulting from distinct neural compensatory mechanisms [Hogeveen, Krug, Geddert, Ragland, & Solomon, 2020].…”
Section: Introductionmentioning
confidence: 99%